Analysis system for emotional behavior in football (ASEB-F): matches of FC Red Bull Salzburg without supporters during the COVID-19 pandemic - Leitner, M.; Richlan, F. (Humanities and Social Sciences Communications, 2021)
During the COVID-19 pandemic the "Austrian Bundesliga"—as in many other European football leagues—resumed the season around the end of May 2020 without supporters in the stadiums. These so-called "ghost games" represent a unique and unprecedented opportunity to study the effects of the (missing) audience on the behavior and experience of sports professionals. The present study is the first of its kind, aimed at addressing the psychological effects of these "ghost games" on football players, staff, and officials. The newly developed "Analysis System for Emotional Behavior in Football" (ASEB-F) was used to video analyze and compare the behavior of players, staff, and officials in—in sum—20 games of FC Red Bull Salzburg in the "Championship Groups" of season 2018/19 ("regular games") and season 2019/20 ("ghost games"). Additionally, the two seasons were compared based on official matchday statistics. Overall, there were 19.5% fewer emotional situations in "ghost games" than in "regular games". The results further show a relative increase in the number of emotional behaviors "Self-Adaptor" (+0.8%), "Protest" (+4.2%), and "Fair-Play-Behavior" (+3.1%) in "ghost games", whereas "Words fight" (-5.1%) and "Discussion" (-5.1%) decreased in "ghost games". In "regular games" referees were actively involved in 39.4% of all documented emotional situations, whereas in "ghost games" referees were actively involved in only 25.2% of all documented emotional situations (-14.2%). Chronological analysis within games—from kick-on to kick-off—further shows substantial differences in the temporal occurrence of emotional behavior between "regular games" and "ghost games". The study provides unprecedented insights into the effects of missing supporters in the football games during the COVID-19 pandemic on emotional behavior on the pitch. Without the external factor of supporters, players and staff acted more factually and got less carried away with longer-lasting and extensive "Words fights" and "Discussion". The evidence from this study indicates that—from a sport psychological perspective—the absence of supporters has a substantial influence on the experience and behavior of players, staff, and officials alike.